Knowledge, Attitude, and Stigma on Tuberculosis and the Associated Factors for Attitude Among Tuberculosis Contacts in Malaysia - Shin Yee LOH; Rosnani ZAKARIA; Noraini MOHAMAD (Medeniyet Medical Journal)
Objective: Tuberculosis (TB) is an old disease and it has infected millions of people worldwide. Since it is a highly infectious disease, many people became TB contact due to prolonged exposure to a person with TB infection. This group of people is at a higher risk of getting latent and active TB infection, hence a vulnerable group for active TB screening. This study explored the factors that determined the attitude score, the level of knowledge, attitude, and stigma (KAS) regarding TB disease among TB contact. Methods: This cross-sectional study used a validated KAS questionnaire, performed among 338 TB contacts from 5 health clinics in Kedah, Malaysia. The respondents were selected via convenience sampling. Simple and multiple linear regressions were used to analyze the data. Results: The mean KAS scores of participants are 73.5% [standard deviation (SD)=17.06], 83.0% (SD=10.33), and 67.0% (SD=16.72), respectively. Higher income (p=0.001), better knowledge score (p<0.001), and higher stigma score (p=0.003) are the significant associated factors for the attitude score. Conclusions: This study revealed that most of the TB contacts have good knowledge and constructive attitude toward TB prevention and screening, but their level of stigma on TB is high. The implementation of TB education and intervention programs among TB contacts are required especially among low-income groups.